Comparative study on antioxidant, antimicrobial, emulsifying and physico-chemical properties of purified bovine and camel β-casein. (April 2021) - Lajnaf, Roua; Gharsallah, Houda; Attia, Hamadi; Ayadi, M.A.
Abstract: Emulsifying properties and in vitro antioxidant and antimicrobial activities of the isolated camel and bovine β-casein (β-CN) were investigated and compared. Antioxidant assay showed that both β-CN had significant reducing power, iron chelating and antiradical activities especially for camel β-CN. Camel β-CN also exhibited strong antifungal activities against Aspergillus tamarii and Aspergillus sclerotiorum. The maximum emulsion activity was achieved by both β-CN samples at pH 7.0 and 9.0 than 5.0, with higher values for the camel β-CN. This behavior was linked to the relative high electronegative charge and interfacial properties of proteins under conditions away from their isoelectric-point as confirmed by the ζ-potential and interfacial tension measurements. Further, the stability of emulsions decreased at pH 5.0 because of the β-CN precipitation and aggregation despite its high surface hydrophobicity. This study concluded that the camel β-CN has antimicrobial, antioxidant, and techno-functional properties in agricultural and food industries. Highlights: Camel and bovine β-CN were purified from milk by cold-incubation. Camel β-CN showed higher antioxidant activities than bovine β-CN. Camel β-CN exhibited strong antifungal activities against two species of Aspergillus. Camel and bovine β-CN coated oil-droplets better at pH 7.0 and 9.0 relative to 5.0. The maximum Emulsion Activity Index values were observed for camel β-CN.